2000
DOI: 10.1136/bmj.321.7269.1103
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and pneumonia in intensive care patients given ranitidine and sucralfate for prevention of stress ulcer: meta-analysis of randomised controlled

Abstract: Objectives To determine the effectiveness of ranitidine and sucralfate in the prevention of stress ulcer in critical patients and to assess if these treatments affect the risk of nosocomial pneumonia. Design Published studies retrieved through Medline and other databases. Five meta-analyses evaluated effectiveness in terms of bleeding rates (A: ranitidine v placebo; B: sucralfate v placebo) and infectious complications in terms of incidence of nosocomial pneumonia (C: ranitidine v placebo; D: sucralfate v plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(126 citation statements)
references
References 34 publications
2
117
2
5
Order By: Relevance
“…In 47% of these patients there was a growth of Gram-negative bacilli, while in patients with gastric pH < 4, cultures were sterile. A metaanalysis carried out by Messori et al [10] concluded that ranitidine is ineffective in preventing gastrointestinal bleeding and increases the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In 47% of these patients there was a growth of Gram-negative bacilli, while in patients with gastric pH < 4, cultures were sterile. A metaanalysis carried out by Messori et al [10] concluded that ranitidine is ineffective in preventing gastrointestinal bleeding and increases the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is difficult to recommend against H 2 blockers or proton pump inhibitors. Sucralafate may indeed be superior from the viewpoint of VAP, but it is less effective with regard to prophylaxis of gastrointestinal bleeding, and thus it use is not warranted over H 2 blockers or proton pump inhibitors (16,37,143).…”
Section: Preventionmentioning
confidence: 99%
“…According to ASHP guidelines on SUP, histamine 2 antagonists (H2-RAs), antacids, and sucralfate are recommended for the prevention of stress ulcers. The choice of the drug is institution-specific [9,[23][24][25][26][27] and should take into account concerns regarding ease of administration, adverse events and cost [4,26,28] . When the ASHP guidelines were published, there was insufficient data available on the efficacy and safety of misoprostol and proton pump inhibitors (PPIs) to allow their recommendation.…”
Section: Data Collectionmentioning
confidence: 99%